Effect of Media Campaigns on Educating (Gen Z) in Saudi Arabia About Sustainable, Eco-Friendly Clothing - Aldabagh, Maha Abdullah; Al-Ahmari, Ihsan Ayed; Qsti, Aroub; Mohammed, Sally; Toffaha, Noura Mohammed (Advances in Social Sciences Research Journal, 2024)
This study sought to assess the level of familiarity among Generation Z in Saudi Arabia with the concept of eco-friendly clothing, and identify the type of media campaigns that have the most significant impact on the purchasing decisions of Generation Z. The study employed the descriptive research design and utilized quantitative analysis to analyze the collected data. The study focused on the Generation Z age group, which was sampled using non-probability purposive sampling techniques. The study found that Gen Z of Jeddah has a moderate to high level of familiarity with eco-friendly clothing. Social media is frequently the primary source of knowledge for eco-fashion for Gen Z. However, despite their heavy use of social media, Gen Z needs more information on sustainable fashion. As a result, more social media campaigns are needed to further educate and update Gen Z on sustainable fashion consumption.